2006
DOI: 10.1007/s00540-006-0412-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia decreases ethanol MAC in rats

Abstract: Despite the known capacity of hypothermia to increase anesthetic potency (decrease the partial pressure required to produce anesthesia), many in vitro studies examine the effects of ethanol and other anesthetics in oocytes or isolated neurons at room temperature. We tested whether, as predicted for potent inhaled anesthetics, a proportionate increase in solubility with hypothermia matched a decrease in ethanol minimum alveolar concentration (MAC), and thereby made the use of a single anesthetic concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, the butane concentration used in these other studies is actually much less than MAC. Anesthetic potency increases approximately 5% per °C decrease in body temperature (Won et al 2006), and applying this correction to rat MAC measurements at 37°C reported in the present study, the estimated butane MAC for rats at 23°C is 11.6% of an atmosphere. This butane partial pressure produces a 310 μM butane concentration in the frog Ringer’s solution at this same temperature, more than double the previously-assumed MAC concentration.…”
Section: Discussionmentioning
confidence: 67%
“…However, the butane concentration used in these other studies is actually much less than MAC. Anesthetic potency increases approximately 5% per °C decrease in body temperature (Won et al 2006), and applying this correction to rat MAC measurements at 37°C reported in the present study, the estimated butane MAC for rats at 23°C is 11.6% of an atmosphere. This butane partial pressure produces a 310 μM butane concentration in the frog Ringer’s solution at this same temperature, more than double the previously-assumed MAC concentration.…”
Section: Discussionmentioning
confidence: 67%
“…23 Second, most drugs require a specific shape, size, and/or polarity in order to interact with specific cell ligands and produce a pharmacologic effect. Yet there is no conserved structural motif among inhaled anesthetics, which include compounds as diverse as single atoms (xenon), 24 short and long chain alcohols, 25,26 and endogenous byproducts of metabolism (CO 2 , 27 ammonia, 28 and ketones 29 ), in addition to the contemporary and historical conventional agents.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Increasing body temperature increases membrane fluidity and anesthetic requirement, whereas decreasing body temperature decreases membrane fluidity and MAC. 26,32 Moreover, some extremely hydrophobic compounds that should exhibit anesthetic potency based on their lipid solubility are actually unable to produce immobility, and are appropriately named “nonimmobilizers.” 21 …”
Section: Mechanisms Of Actionmentioning
confidence: 99%